Profilicollis altmani (Perry, 1942) Van Cleave, 1947 (Acanthocephala) in Perú. With notes on the experimental infection of terretrial mammals - Tantaleán, Manuel (2002)
A survey was made of sand crab, Emerita analoga Stimpson (Hippidae), collected at Bujama beach (Mala, Lima) January-February, 2001. From 37 to 48% of them harbored cystacanths identified as Profilicollis altmani (Perry, 1942) Van Cleave, 1947. Otherwise, a number of these cystacanths were inoculated to rats, mice, hamsters and a pup. All animals were infected. The acanthocephalan was found in the abdominal cavity and/or wall of the small and large intestine. Man may become infected with P. altmani by eating infected sand crabs.